Untargeted metabolomic profiling of Pseudocnella sykion from KwaZulu-Natal, South Africa using 1H-NMR and UPLC-QTOF-HR-MS - Upton, Cassandra; Prinsloo, Gerhard; Steenkamp, Paul Anton; Okpeku, Moses (Frontiers in Marine Science, 2025)
IntroductionSea cucumbers are ecologically and economically significant marine invertebrates, yet the metabolic diversity and bioactive potential of noncommercialized, endemic species remains poorly understood.MethodsThis study presents the first intra-species metabolomic analysis of Pseudocnella sykion, a species endemic to the Eastern coast of Southern Africa, using untargeted 1HNMR metabolomics and full-scan UPLC-QTOF-HR-MS.ResultsThe analysis revealed a diverse array of metabolites associated with protein synthesis, tissue growth, osmoregulation, and energy utilization, with distinct tissue-specific patterns across the body wall, gonad, and gut/mesentery. The gut/mesentery tissue showed higher levels of amino acids and energy-related compounds. UPLCQTOF-HR-MS tentatively identified several metabolites, including triterpene glycosides and rosmarinic acid, a phenolic compound typically associated with plants. Online resources, including the Dictionary of Marine Natural Products, contained no previously recorded compounds for P. sykion.DiscussionThese findings underscore the untapped potential of P. sykion as a source of novel metabolites and demonstrate the utility of untargeted metabolomics in generating baseline profiles for underexplored marine species. The results offer a foundation for future research into bioactivity, environmental monitoring, and cultivation strategies. While this study provides critical baseline data, challenges in metabolite identification and extraction underscore the need for further targeted analyses. Overall, this research enhances our understanding of the metabolic dynamics of sea cucumbers and advocates for continued exploration of lesser-known species to support conservation, bioprospecting, and sustainable aquaculture. It represents a pioneering effort in metabolomic profiling of Southern African sea cucumber species and lays the groundwork for future investigations into their metabolic pathways and potential bioactivities.